2018
DOI: 10.1089/jwh.2017.6878
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depressive Relapse in Women Undergoing Infertility Treatment

Abstract: Risk of depressive relapse among women undergoing ART is considerable. Medication continuation does not adequately confer relapse prevention. Stress and inflammation appear to contribute to risk of relapse. Additional strategies to mitigate depressive relapse in at-risk women undergoing ART are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 36 publications
0
11
0
3
Order By: Relevance
“…Moreover, further evidence has demonstrated a direct link between inflammatory processes and rMDD [17]. For instance, Freeman et al demonstrated that CRP levels were associated with depression relapse (odds ratio = 1.92; 95% confidence interval 1.43–2.55; p < 0.0001), suggesting that inflammation contributes to the risk of relapse [33]. Copeland et al also demonstrated that cumulative episodes predict changes in CRP levels independently, although body mass index, nicotine use, and recent infections were partial mediators of the effect of cumulative episodes on CRP levels [34].…”
Section: Link Between Inflammation and Rmddmentioning
confidence: 99%
“…Moreover, further evidence has demonstrated a direct link between inflammatory processes and rMDD [17]. For instance, Freeman et al demonstrated that CRP levels were associated with depression relapse (odds ratio = 1.92; 95% confidence interval 1.43–2.55; p < 0.0001), suggesting that inflammation contributes to the risk of relapse [33]. Copeland et al also demonstrated that cumulative episodes predict changes in CRP levels independently, although body mass index, nicotine use, and recent infections were partial mediators of the effect of cumulative episodes on CRP levels [34].…”
Section: Link Between Inflammation and Rmddmentioning
confidence: 99%
“…We did not find any clinical trial specifically investigating the effects of hormonal treatments on depressive symptoms in unipolar or bipolar disorder patients. In a recent prospective observational study that included women receiving infertility treatments with a history of major depressive disorder or bipolar disorder (24), a high risk of depressive relapse was found, even in those women maintaining psychotropic medication. These results suggest that maintenance of medication is not sufficient to avoid affective relapses.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women did not differ in depressive symptoms compared to the other two groups, suggesting a lack of negative effect of fertility treatments on psychopathological symptoms. More recently, Freeman et al (24) carried out a prospective observational study in women with a previous history of unipolar or bipolar depression undergoing fertility treatment (24). They concluded that maintenance of psychotropic medication was not sufficient for avoiding affective recurrences.…”
Section: Introductionmentioning
confidence: 99%
“…Association between psychological stress(such as depression and anxiety) and male or female infertility has been reported [14,15] , and the impact of psychological stress on women has been well analyzed [16][17][18] ]. However, the association of psychological stress and male semen parameters has not yet been fully studied [19] .…”
Section: Introductionmentioning
confidence: 99%